2017
DOI: 10.4236/fns.2017.81009
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Chemical and Organoleptical Characteristics of Low-Calorie Fruit Nectars Incorporating Stevioside as a Natural Sweetener

Abstract: The study is aiming at preparation of low-calorie fruit nectars for diabetes and weight maintaining approaches as well as consumer satisfaction. Therefore, twenty low-calorie fruit-based formulated nectars were prepared mainly from orange, pomegranate, guava and mango pulps which sweetened with sucrose or sucrosereplaced at 25%, 50%, 75% and 100% using stevioside. Primitively, the yield of fresh fruits had been calculated. Consequently, nutritional, chemical and organoleptical characteristics of prepared fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As described in Figure 2, minor increase in TTA was observed during the storage period, the values were ranged from (0.57–0.65) g/100 ml to (0.80–0.90) g/100 ml at 4°C and around (0.6–0.67) g/100 ml to (0.85–0.91) g/100 ml at 25°C. This data were in accordance with Barakat et al (2017), Hosseini et al (2015) who have reported the increment of TTA to the partial degradation of pectin. This increment can be also harmonized with either the antimicrobial potential of Stevia and orange juice composition according to Pina‐Pérez et al (2018) and Haraoui et al (2019).…”
Section: Resultssupporting
confidence: 93%
“…As described in Figure 2, minor increase in TTA was observed during the storage period, the values were ranged from (0.57–0.65) g/100 ml to (0.80–0.90) g/100 ml at 4°C and around (0.6–0.67) g/100 ml to (0.85–0.91) g/100 ml at 25°C. This data were in accordance with Barakat et al (2017), Hosseini et al (2015) who have reported the increment of TTA to the partial degradation of pectin. This increment can be also harmonized with either the antimicrobial potential of Stevia and orange juice composition according to Pina‐Pérez et al (2018) and Haraoui et al (2019).…”
Section: Resultssupporting
confidence: 93%
“…However, sucrose as traditional sweetener used to jelly products is high calorie (Cha et al., 2014; Lee et al., 2010), and low-calorie sweeteners are pursued (Kroger et al., 2006). Stevioside is a new type of natural sweetener, which is derived from leaves of Stevia rebaudiana Bertoni (Barakat et al., 2017). Its relative sweetness is about 200–300 times higher than sucrose, but the caloric value is only about 1/250 of sucrose, which is not involved in the metabolism of the human body after ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Chocolate can provide energy for human relatively quicker than food. Chocolate contains non‐fat particles (sugar, skim milk powder, cocoa solids, and emulsifier) which are dispersed in cocoa butter (CB) as a continuous fat phase (Barakat et al., 2017; Lagast et al., 2018). Despite the high sugar and fat content of chocolates, consumption of them plays a positive role in human nutrition through antioxidants, especially polyphenols including flavonoids such as epicatechin, catechin, and significantly procyanidins (Oroian & Escriche, 2015).…”
Section: Introductionmentioning
confidence: 99%